Nickel-catalysed synthesis of multisubstituted pyrroles by anti-carbometallative cyclisations - Gillbard, Simone Marie (2019)
Herein is presented the first example of nickel-catalysed cyclisation of Ntosylalkynamides with arylboronic acids to give 2,3,4-trisubstituted pyrroles. The reaction is initiated by alkyne arylnickelation and proceeds via an essential E/Z isomerisation step which allows for cyclisation. An investigation of the scope of the reaction and the boronic acid gave rise to 25 examples in 46-99% yield.